Effect of different levels of fortification of wheat flour with defatted coconut flour on the quality of fibre-enriched biscuits - J. M. N. Marikkar; J. M. M. A. Jayasundara; A. P. D. Rupanjali; M. N. D. Fernandopulle (International Coconut Community Journal, 2007)
Defatted coconut flour obtained from the whitish kernel residue left after the extraction of virgin coconut oil has potential application in high protein-fiber enriched food products. A study was conducted to investigate the use of defatted coconut flour in the preparation of fiber-enriched biscuits. In this, wheat flour was fortified with defatted coconut flour in varying proportions (w/w, 0, 10, 20, 30, 40, 50, 60, and 70%) to prepare a series of blends for biscuit dough. Biscuits samples prepared according to a standard recipe were evaluated by a 36-member semi-trained panel using a 7-point hedonic scale to determine the critical limit of defatted coconut flour substitution in wheat flour for acceptable quality biscuits. Results showed that defatted coconut flour could be used to substitute wheat flour up to a level of 40% without affecting the overall quality. At this level, the dietary fiber content of the biscuit was found to increase by about 10 times. Although biscuit samples showed good acceptability at the beginning, their keeping quality decreased with the increasing level of defatted coconut flour in the biscuit formulation.